Application of GIS in Evaluating Suitable Clam Farming Site in Vembanad Lake, India - Nagampoozhi, Suja (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present study identifies and quantifies appropriate sites for black clam farming in the Vembanad Lake using a geographical information system (GIS). The black clam, Villorita cpyrinoides, is the most important clam landed in India. Despite being a candidate species for aquaculture, the trials on farming of clams are very limited. The aim of this study was to select the most suitable sites for clam farming in Vembanad Lake based on the use of GIS-based models. For this, the importance of soil quality, water quality and infrastructure facilities were accessed using an analytical hierarchical process. The site suitability map was prepared using each attribute and divided into four classes, such as most suitable, moderately suitable, least suitable and poor. Water quality is found to play a major role (54%) compared to soil quality (24%) and infrastructure facilities (22%) for development of clam farms in Vembanad Lake. Salinity registered the highest importance (0.21) for the water quality suitability map as compared to other parameters like pH and dissolved oxygen. The total area covered under this study was 6471 ha out of which, 3121 ha (48%) was identified as most suitable and of the remaining 3350 ha, 1804 ha (28%) was identified as moderately suitable, 946 ha (15%) was identified as least suitable and 600 ha (9%) was identified as the poor site for clam farming in Vembanad Lake.